Analysis of the Status of Village Apparatus Personnel in the Village Government System Reviewed from Law Number 3 of 2024 concerning the Second Amendment to Law Number 6 of 2014 concerning Villages - Agustin, Eka Wulandari; Saliman, Abdul Rasyid; Agustina, Enny; Oktavianingrum, Fabiola Nurul (GoAcademica Research & Publishing, 2025)
This study analyzes the status of village apparatus personnel in the village government system in Indonesia, especially from the perspective of legal certainty and state administrative law. Although village officials play an important role in public services at the village government level, uncertainty regarding the status of village officials, especially whether village officials are recognized as State Civil Apparatus (ASN) or Government Employees with Employment Agreements (PPPK), pose problems in aspects of welfare, career stability, and service professionalism. This study uses a normative juridical analysis method, this study examines the role of the state in providing clear legal guarantees for village officials through the formation of specific regulations with an approach to analysis, legislation and case studies. Based on the findings of the research, the need for the formulation of policies that recognize village apparatus as part of ASN or PPPK, as well as the regulation of welfare and work capacity of village apparatus, is an important recommendation to increase the effectiveness of village government based on the principle of legal certainty and state administrative law. The conclusions and suggestions from this study are expected to create a more transparent, accountable, and professional village government, in accordance with the goal of village autonomy mandated by Law Number 6 of 2014 concerning Villages and its latest changes.